Preparation method and application of gypsum silica gel composite photocatalyst particles

Photocatalytic particles are prepared by combining gypsum with silicon gel, combining titanium dioxide and silicon sol, and solving the complex and cost-effective preparation of existing photocatalytic materials, achieving high-efficiency and low-cost photocatalytic effects, and broadening the application field of gypsum .

CN119236973APending Publication Date: 2025-01-03BEIJING YIXING TECH CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411496827.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing photocatalytic materials have complex preparation processes and high costs, resulting in a lack of photocatalyst products with reasonable prices and high degradation efficiency on the market. The application areas of gypsum are reduced, and it is necessary to broaden their application areas and reduce the preparation costs.

Method used

Photocatalytic particles are prepared by composite gypsum and silicon gel. Through granulation, screening, drying and spraying processes, combined with titanium dioxide photocatalyst and silica sol, gypsum/silica gel composite photocatalytic particles with high degradation efficiency are formed.

Benefits of technology

It realizes low-cost and high-efficiency photocatalytic particles preparation, excellent performance, degradation efficiency of more than 90%, simple process, and suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236973A_ABST
    Figure CN119236973A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of gypsum silica gel composite photocatalytic particles, photocatalytic particles with the degradation efficiency of 90% or above can be prepared at low cost, the photocatalytic particles have the characteristics of excellent performance, low production cost and the like, and the application value of gypsum is further improved, the preparation method comprises the following steps: S1, granulating based on gypsum powder and water through a granulator to obtain gypsum particles; s2, screening and drying the gypsum particles; s3, preparing titanium dioxide photocatalytic slurry; s4, preparing titanium dioxide photocatalytic slurry containing silica sol; and S5, preparing the gypsum silica gel composite photocatalytic particles. The invention further discloses application of the preparation method of the gypsum silica gel composite photocatalytic particles in photocatalytic reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photocatalysis technology, and more specifically, to a preparation method and application of gypsum / silicone gel composite photocatalytic particles. Background Art

[0002] In recent years, with the gradual development of economy and society, the national construction industry has continued to develop, and the market has developed rapidly for the national industry and manufacturing industry, but the air pollution in life has gradually attracted people's attention. Therefore, high-quality photocatalytic products are indispensable. In the market, photocatalytic purification technology has been combined with traditional decorative materials such as coatings, wallpapers, and lamps, and some new purification functional materials have been developed, but due to the complexity of the preparation process and the high cost of the carrier, the price is relatively high. Therefore, it is inevitable to prepare photocatalyst products with high degradation efficiency, low price and market trend. Gypsum is a widely used industrial material and building material. It has huge reserves and is widely used in cement retarders, building products, model making, medical food additives, fillers, etc. However, due to the gradual decline of the construction industry, the output of gypsum has gradually decreased, and the application field has been further reduced. Therefore, it is of great significance to increase the application field of gypsum.

[0003] Gypsum has a certain hardness after hydration. Under the microscopic view, the hardened gypsum is mostly fibrous accumulation with many pores. The fibrous nature of gypsum after hydration makes it possible to use it as a carrier to prepare photocatalytic materials. For example, Patent ZL201910410735.4 discloses a gypsum board with adsorption and photocatalytic properties, its preparation method and application. The performance of this material mainly comes from the titanium dioxide in the raw materials, but the catalytic efficiency is not high enough; Tian Yu (Beijing University of Chemical Technology) prepared a zinc-loaded photocatalyst using gypsum as a carrier, which can degrade 90% of methylene blue within 6 hours of visible light, but the preparation process is complicated.

[0004] Silica sol is an aqueous solution of nano-silicon dioxide, which can form a colorless, transparent, strong, and rich pore structure silica gel after dehydration and drying. Therefore, in order to further expand the application field of gypsum, it is of great significance to prepare a gypsum / silica gel composite photocatalytic product with low cost, simple process, and high photocatalytic efficiency. Summary of the invention

[0005] In order to solve the technical defects and deficiencies in the prior art, the present invention provides the following technical solution: a method for preparing gypsum silicone gel composite photocatalytic particles and applications thereof, which can prepare photocatalytic particles with a degradation efficiency of more than 90% at low cost, have the characteristics of excellent performance and low production cost, thereby improving the application value of gypsum.

[0006] In one aspect, the present invention provides a method for preparing gypsum silica gel composite photocatalytic particles, comprising:

[0007] S1, granulating gypsum powder and water to obtain gypsum particles by a granulator;

[0008] S2, screening and drying the gypsum particles;

[0009] S3, preparing titanium dioxide photocatalytic slurry;

[0010] S4, preparing titanium dioxide photocatalytic slurry containing silica sol;

[0011] S5, preparing gypsum silica gel composite photocatalytic particles.

[0012] Preferably, the S1 comprises:

[0013] S11, placing gypsum powder in a granulator;

[0014] S12, adding a certain amount of water to the gypsum powder to form a first mixture;

[0015] S13, granulating the first mixture to obtain gypsum particles.

[0016] Preferably, the mass ratio of the gypsum powder to the water is gypsum powder: water = 100: (10-20); the rotation speed of the granulator is 60 r / min-120 r / min, and the granulation temperature is 15° C.-35° C.; the size of the gypsum particles obtained after the granulation is Φ0.5 mm-6 mm.

[0017] Preferably, S2 includes:

[0018] S21, placing the gypsum particles on a sieve for screening to obtain gypsum particles of a suitable particle size;

[0019] S22, placing the gypsum particles of the required particle size in an oven for drying.

[0020] Preferably, the size of the sieve is 4-16 mesh, the particle size of the gypsum-based particles that meet the particle size is Φ1mm-5mm, the drying temperature is 70°C-105°C, and the drying time is 3h-12h.

[0021] Preferably, S3 includes:

[0022] S31, mixing titanium dioxide photocatalyst and water to obtain a first mixture; the material ratio in the first mixture is titanium dioxide photocatalyst: water mass ratio = (10-30): 100;

[0023] S32, stirring the first mixture to obtain titanium dioxide photocatalytic slurry.

[0024] Preferably, the stirring speed of the first mixture is

[0025] The stirring speed of the first mixture is 300r / min to 1000r / min, the stirring time of the first mixture is 1min to 5min, and the stirring temperature of the first mixture is 15°C to 35°C.

[0026] Preferably, S4 includes:

[0027] S41, mixing the titanium dioxide photocatalytic slurry and silica sol to obtain a second mixture; the concentration of the silica sol is 30% to 50%; the material ratio in the second mixture is titanium dioxide photocatalytic slurry:

[0028] Mass ratio of silica sol = (10-100): 100;

[0029] S42, stirring the second mixture to obtain a titanium dioxide photocatalytic slurry containing silica sol. Preferably, the stirring speed of the second mixture is

[0030] The stirring speed of the second mixture is 100 r / min to 300 r / min, the stirring time of the second mixture is 1 min to 3 min; the stirring temperature of the second mixture is 15° C. to 35° C.

[0031] Preferably, S5 includes:

[0032] S51, placing the sieved and dried gypsum particles on a 40-mesh sieve;

[0033] S52, spraying the gypsum particles with the titanium dioxide photocatalytic slurry containing silica sol to obtain gypsum silica sol composite photocatalytic particles;

[0034] S53, placing the obtained gypsum silica sol composite photocatalytic particles in an oven for drying, and after drying, gypsum silica gel composite photocatalytic particles with a particle size of 1.7 mm to 4.2 mm can be obtained.

[0035] Preferably, the spraying rate is 1 s / time to 20 s / time, the spraying time is 1 min to 20 min, and the spraying temperature is 15°C to 35°C; the drying temperature is 50°C to 80°C, and the drying time is 2h to 12h.

[0036] The second aspect of the present invention is to provide the application of the preparation method of the gypsum silica gel composite photocatalytic particles of the first aspect in a photocatalytic reaction.

[0037] Beneficial effects of the present invention:

[0038] (1) Innovatively utilizing the hydration hardening and micro-fibrous structural properties of gypsum, gypsum particles with a certain strength are obtained, and then a titanium dioxide photocatalytic slurry containing silica sol is loaded on the surface. Among them, the silica sol plays a role in enhancing the mechanical properties and enriching the surface pore structure, thereby preparing a gypsum / silica gel composite photocatalytic particle. The particle has the advantages of excellent mechanical properties and high degradation efficiency, and also has the advantages of simple process, low cost, and easy industrialization.

[0039] (2) The preparation method has a simple process flow, the photocatalytic particles prepared by granulation have excellent performance, and the production cost is low. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a flow chart of the method for preparing the gypsum silica gel composite photocatalytic particles provided by the present invention.

[0041] Figure 2 The flowchart of step S1 provided by the present invention.

[0042] Figure 3 The flowchart of step S2 provided by the present invention.

[0043] Figure 4 The flowchart of step S3 provided by the present invention.

[0044] Figure 5 The flowchart of step S4 provided by the present invention.

[0045] Figure 6 This is a flow chart of step S5 provided by the present invention. DETAILED DESCRIPTION

[0046] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0047] like Figure 1-6 As shown, the first aspect of this embodiment provides a method for preparing gypsum silica gel composite photocatalytic particles, comprising the following steps:

[0048] S1, granulating gypsum powder and water to obtain gypsum particles by a granulator;

[0049] As a preferred embodiment, the S1 includes:

[0050] S11, placing gypsum powder in a granulator;

[0051] S12, adding a certain amount of water to the gypsum powder to form a first mixture;

[0052] S13, granulating the first mixture to obtain gypsum particles.

[0053] As a preferred embodiment, the mass ratio of the gypsum powder to the water is gypsum powder: water = 100: (10-20).

[0054] As a preferred embodiment, the rotation speed of the granulator is 60 r / min to 120 r / min, and the granulation temperature is 15°C to 35°C.

[0055] As a preferred embodiment, the size of the gypsum particles obtained after the granulation is Φ0.5 mm to 6 mm.

[0056] As a more preferred embodiment, a water-to-paste ratio that is too high will affect the granulation shape, and a water-to-paste ratio that is too low will affect the gypsum strength. A granulator speed that is too low or too high will result in unsatisfactory granule forming. Therefore, the mass ratio of the gypsum powder to the water is gypsum powder: water = 100: (12-15), the granulator speed is 80 r / min-100 r / min, and the granulation temperature is 20°C-30°C; the gypsum particles obtained after granulation have a size of Φ1mm-5mm.

[0057] S2, screening and drying the gypsum particles;

[0058] As a preferred embodiment, S2 includes:

[0059] S21, placing the gypsum particles on a sieve for screening to obtain gypsum particles of a suitable particle size;

[0060] S22, placing the gypsum particles of the required particle size in an oven for drying.

[0061] As a preferred embodiment, the size of the sieve is 4-16 mesh, the particle size of the gypsum-based particles that meet the particle size is Φ1mm-5mm, the drying temperature is 70°C-105°C, and the drying time is 3h-12h.

[0062] As a more preferred embodiment, the size of the sieve is 5-10 mesh, and the particle size needs to be moderate, so the particle size of the gypsum particles obtained after screening is Φ1.7mm-4.1mm, the drying temperature is 85℃-95℃, and the drying time is 4h-5h.

[0063] S3, preparing titanium dioxide photocatalytic slurry;

[0064] As a preferred implementation, S3 includes:

[0065] S31, mixing titanium dioxide photocatalyst and water to obtain a first mixture; the material ratio in the first mixture is titanium dioxide photocatalyst: water mass ratio = (10-30): 100;

[0066] As a more preferred embodiment, the material ratio in the first mixture is the mass ratio of titanium dioxide photocatalyst: water = (20-30): 100;

[0067] S32, stirring the first mixture to obtain titanium dioxide photocatalytic slurry.

[0068] As a preferred embodiment, the stirring speed of the first mixture is 300 r / min to 1000 r / min, the stirring time of the first mixture is 1 min to 5 min, and the stirring temperature of the first mixture is 15° C. to 35° C.

[0069] As a more preferred embodiment, the stirring speed of the first mixture is 500 r / min to 700 r / min, the stirring time of the first mixture is 3 min, and the stirring temperature of the first mixture is 20° C. to 30° C.

[0070] S4, preparing titanium dioxide photocatalytic slurry containing silica sol;

[0071] As a preferred implementation, S4 includes:

[0072] S41, mixing the titanium dioxide photocatalytic slurry and silica sol (the source of this embodiment: Dezhou Jinghuo Technology Glass Co., Ltd., the main component is: SiO2·nH2O, the concentration of silica sol refers to the mass fraction of silicon dioxide in the solution, the same below) to obtain a second mixture; the concentration of the silica sol is 30% to 50%; the material ratio in the second mixture is the mass ratio of titanium dioxide photocatalytic slurry: silica sol

[0073] =(10~100):100;

[0074] As a more preferred embodiment, the concentration of the silica sol is 40% to 50%; the material ratio in the second mixture is the mass ratio of titanium dioxide photocatalytic slurry: silica sol

[0075] =(30~50):100;

[0076] S42, stirring the second mixture to obtain titanium dioxide photocatalytic slurry containing silica sol.

[0077] As a preferred embodiment, the stirring speed of the second mixture is 100 r / min to 300 r / min, the stirring time of the second mixture is 1 min to 3 min; and the stirring temperature of the second mixture is 15° C. to 35° C.

[0078] As a more preferred embodiment, the stirring speed of the second mixture is 200 r / min, the stirring time of the second mixture is 2 min, and the stirring temperature of the second mixture is 20° C. to 30° C. This is because too fast a stirring speed or too long a stirring time of the silica sol and the photocatalyst will destroy the sol, affect the formation of the gel, and cause a decrease in the photocatalytic strength and degradation efficiency.

[0079] S5, preparing gypsum silica gel composite photocatalytic particles.

[0080] As a preferred implementation, S5 includes:

[0081] S51, placing the sieved and dried gypsum particles on a 40-mesh sieve;

[0082] S52, spraying the gypsum particles with the titanium dioxide photocatalytic slurry containing silica sol to obtain gypsum silica sol composite photocatalytic particles;

[0083] S53, placing the obtained gypsum silica sol composite photocatalytic particles in an oven for drying, and after drying, gypsum silica gel composite photocatalytic particles with a particle size of 1.7 mm to 4.2 mm can be obtained.

[0084] As a preferred embodiment, the spraying rate is 1 s / time to 20 s / time, the spraying time is 1 min to 20 min, and the spraying temperature is 15°C to 35°C.

[0085] As a preferred embodiment, the drying temperature is 50° C. to 80° C., and the drying time is 2 h to 12 h.

[0086] As a more preferred implementation mode, if the spraying rate is too frequent, the silica sol will not easily adhere to the surface, and if the spraying rate is too slow, the process time will be increased; if the spraying time is too short, less catalyst will be attached, and if the time is too long, the molding shape will be irregular. Therefore, the spraying rate is 10s / time to 15s / time, the spraying time is 10min to 15min, and the spraying temperature is 20℃ to 30℃.

[0087] As a more preferred embodiment, too high a drying temperature and too long a drying time will destroy the photocatalyst and the silica sol structure, and reduce the photocatalytic performance and mechanical properties. Therefore, the drying temperature is 55°C to 65°C, and the drying time is 3h to 4h.

[0088] The second aspect of this embodiment is to provide the application of the preparation method of the gypsum silica gel composite photocatalytic particles of the first aspect in a photocatalytic reaction.

[0089] Application Examples

[0090] Example 1

[0091] This embodiment provides a method for preparing gypsum / silicone gel composite photocatalytic particles, comprising the following steps:

[0092] 1) Place gypsum powder in a granulator, add a certain amount of water for granulation, and obtain gypsum particles. Ratio: gypsum powder: water = 100:10, granulator speed 60r / min, granulation temperature 15°C; the size of the gypsum particles obtained after granulation is Φ0.5mm~6mm.

[0093] 2) The particles in step 1) are placed in a sieve to be sieved to obtain gypsum particles of a suitable size, and the gypsum particles of a suitable size are placed in an oven for drying. The size of the sieve used is 4-10 meshes, the size of the gypsum particles of a suitable size is Φ1.7mm-5mm, and the particle size of the gypsum-based particles obtained after granulation is Φ1.7mm-5mm, the drying temperature is 70°C, and the drying time is 3h.

[0094] 3) Mixing the titanium dioxide photocatalyst and water and stirring to obtain a titanium dioxide photocatalytic slurry. The stirring speed is 300 r / min, the stirring time is 1 min, and the stirring temperature is 15°C.

[0095] Ratio: Titanium dioxide photocatalyst: water

[0096] =10:100

[0097] 4) The titanium dioxide photocatalytic slurry and silica sol in 3) are mixed and stirred to obtain a titanium dioxide photocatalytic slurry containing silica sol, the silica sol concentration is 30%, the stirring speed is 100 r / min, the stirring time is 1 min, and the stirring temperature is 15°C.

[0098] Ratio: Titanium dioxide photocatalytic slurry: Silica sol

[0099] =10:100

[0100] 5) Place the gypsum particles in 2) in a 40-mesh medium, and spray with the titanium dioxide photocatalytic slurry containing silica sol in 4) to obtain gypsum / silica sol composite photocatalytic particles. The obtained gypsum / silica sol composite photocatalytic particles are placed in an oven for drying. After drying, gypsum / silica gel composite photocatalytic particles with a particle size of 1.7mm to 5.2mm can be obtained. The spraying rate is 1s / time, the spraying time is 1min, and the spraying temperature is 15°C. The drying temperature is 50°C and the drying time is 2h. Under this process, gypsum / silica gel composite photocatalytic particles with a 24h photocatalytic efficiency of 63% can be obtained.

[0101] Example 2

[0102] This embodiment provides a method for preparing gypsum / silicone gel composite photocatalytic particles, comprising the following steps:

[0103] 1) Placing gypsum powder in a granulator, adding a certain amount of water for granulation, and obtaining gypsum-based photocatalyst particles. Ratio: gypsum powder: water = 100:15, granulator speed 90r / min, granulation temperature 25°C; the size of the gypsum particles obtained after granulation is Φ1mm~5mm.

[0104] 2) The particles in step 1) are placed in a sieve to be sieved to obtain gypsum particles of a suitable size, and the gypsum particles of a suitable size are placed in an oven for drying. The size of the sieve used is 5-10 meshes, and the particle size of the gypsum-based particles obtained after granulation is 1.7 mm to 4.0 mm. The drying temperature is 90° C. and the drying time is 4 hours.

[0105] 3) Mixing the titanium dioxide photocatalyst and water and stirring to obtain a titanium dioxide photocatalytic slurry. The stirring speed is 700 r / min, the stirring time is 3 min, and the stirring temperature is 25°C.

[0106] Ratio: Titanium dioxide photocatalyst: water

[0107] =20:100

[0108] 4) The titanium dioxide photocatalytic slurry and silica sol in 3) are mixed and stirred to obtain a titanium dioxide photocatalytic slurry containing silica sol, the silica sol concentration is 40%, the stirring speed is 200 r / min, the stirring time is 2 min, and the stirring temperature is 25°C.

[0109] Ratio: Titanium dioxide photocatalytic slurry: Silica sol

[0110] =50:100

[0111] 5) Place the gypsum particles in 2) in a 40-mesh medium, and spray with the titanium dioxide photocatalytic slurry containing silica sol in 4) to obtain gypsum / silica sol composite photocatalytic particles. The obtained gypsum / silica sol composite photocatalytic particles are placed in an oven for drying. After drying, gypsum / silica gel composite photocatalytic particles with a particle size of 1.7mm to 5.2mm can be obtained. The spraying rate is 10s / time, the spraying time is 10min, and the spraying temperature is 25°C. The drying temperature is 60°C and the drying time is 3h. Under this process, gypsum / silica gel composite photocatalytic particles with a 24h photocatalytic efficiency of 90% can be obtained.

[0112] Example 3

[0113] This embodiment provides a method for preparing gypsum / silicone gel composite photocatalytic particles, comprising the following steps:

[0114] 1) Placing gypsum powder in a granulator, adding a certain amount of water for granulation, and obtaining gypsum-based photocatalyst particles. Ratio: gypsum powder: water = 100:20, granulator speed 120r / min, granulation temperature 35°C; the size of the gypsum particles obtained after granulation is Φ0.5mm~6mm.

[0115] 2) The particles in step 1) are placed in a sieve to be screened to obtain gypsum particles of a suitable size, and the gypsum particles of a suitable size are placed in a vacuum drying oven for drying. The sieve used is 4-8 mesh, the gypsum particles of a suitable size are Φ2.4mm-5mm, the drying temperature is 105°C, and the drying time is 12h.

[0116] 3) Mixing the titanium dioxide photocatalyst and water and stirring to obtain a titanium dioxide photocatalytic slurry. The stirring speed is 1000 r / min, the stirring time is 5 min, and the stirring temperature is 35°C.

[0117] Ratio: Titanium dioxide photocatalyst: water

[0118] =30:100

[0119] 4) The titanium dioxide photocatalytic slurry and silica sol in 3) are mixed and stirred to obtain a titanium dioxide photocatalytic slurry containing silica sol, with a silica sol concentration of 50%, a stirring speed of 300 r / min, a stirring time of 3 min, and a stirring temperature of 35°C.

[0120] Ratio: Titanium dioxide photocatalytic slurry: Silica sol

[0121] =100:100

[0122] 5) Place the gypsum particles in 2) in a 40-mesh screen and spray with the titanium dioxide photocatalytic slurry containing silica sol in 4) to obtain gypsum / silica sol composite photocatalytic particles. The obtained gypsum / silica sol composite photocatalytic particles are placed in an oven for drying. After drying, gypsum / silica gel composite photocatalytic particles with a particle size of 2.4mm to 5.2mm can be obtained. The spraying rate is 20s / time, the spraying time is 20min, and the spraying temperature is 35°C. The drying temperature is 80°C and the drying time is 12h. Under this process, gypsum / silica gel composite photocatalytic particles with a 24h photocatalytic efficiency of 70% can be obtained.

[0123] Although preferred embodiments of the present invention have been described, additional changes and modifications may be made to these embodiments by those skilled in the art once the basic inventive concepts are known. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention. Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing gypsum silica gel composite photocatalytic particles, characterized in that: include: S1, granulating gypsum powder and water to obtain gypsum particles by a granulator; S2, screening and drying the gypsum particles; S3, preparing titanium dioxide photocatalytic slurry; S4, preparing titanium dioxide photocatalytic slurry containing silica sol; S5, preparing gypsum silica gel composite photocatalytic particles.

2. The method for preparing gypsum silica gel composite photocatalytic particles according to claim 1, characterized in that: The S1 includes: S11, placing gypsum powder in a granulator; S12, adding a certain amount of water to the gypsum powder to form a first mixture; S13, granulating the first mixture to obtain gypsum particles.

3. The method for preparing gypsum silica gel composite photocatalytic particles according to claim 2, characterized in that: The mass ratio of the gypsum powder to the water is gypsum powder: water = 100: (10-20); the rotation speed of the granulator is 60 r / min-120 r / min, and the granulation temperature is 15° C.-35° C.; the size of the gypsum particles obtained after the granulation is Φ0.5 mm-6 mm.

4. The method for preparing gypsum silica gel composite photocatalytic particles according to claim 3, characterized in that: The S2 includes: S21, placing the gypsum particles on a sieve for screening to obtain gypsum particles of a suitable particle size; S22, placing the gypsum particles of the required particle size in an oven for drying.

5. The method for preparing gypsum silica gel composite photocatalytic particles according to claim 4, characterized in that: The size of the sieve is 4-16 mesh, the particle size of the gypsum-based particles that meet the particle size is Φ1mm-5mm, the drying temperature is 70°C-105°C, and the drying time is 3h-12h.

6. The method for preparing gypsum silica gel composite photocatalytic particles according to claim 5, characterized in that: The S3 includes: S31, mixing titanium dioxide photocatalyst and water to obtain a first mixture; the material ratio in the first mixture is titanium dioxide photocatalyst: water mass ratio = (10-30): 100; S32, stirring the first mixture to obtain titanium dioxide photocatalytic slurry.

7. The method for preparing gypsum silica gel composite photocatalytic particles according to claim 6, characterized in that: The stirring speed of the first mixture is 300 r / min to 1000 r / min, the stirring time of the first mixture is 1 min to 5 min, and the stirring temperature of the first mixture is 15° C. to 35° C.

8. The method for preparing gypsum silica gel composite photocatalytic particles according to claim 7, characterized in that: The S4 includes: S41, mixing the titanium dioxide photocatalytic slurry and silica sol to obtain a second mixture; the concentration of the silica sol is 30% to 50%; the material ratio in the second mixture is titanium dioxide photocatalytic slurry: Mass ratio of silica sol = (10-100): 100; S42, stirring the second mixture to obtain titanium dioxide photocatalytic slurry containing silica sol.

9. The method for preparing gypsum silica gel composite photocatalytic particles according to claim 8, characterized in that: The stirring speed of the second mixture is 100 r / min to 300 r / min, the stirring time of the second mixture is 1 min to 3 min, and the stirring temperature of the second mixture is 15° C. to 35° C.

10. The method for preparing gypsum silica gel composite photocatalytic particles according to claim 9, characterized in that: The S5 includes: S51, placing the sieved and dried gypsum particles on a 40-mesh sieve; S52, spraying the gypsum particles with the titanium dioxide photocatalytic slurry containing silica sol to obtain gypsum silica sol composite photocatalytic particles; S53, placing the obtained gypsum silica sol composite photocatalytic particles in an oven for drying, and after drying, gypsum silica gel composite photocatalytic particles with a particle size of 1.7 mm to 4.2 mm can be obtained.

11. The method for preparing gypsum silica gel composite photocatalytic particles according to claim 10, characterized in that: The spraying rate is 1s / time to 20s / time, the spraying time is 1min to 20min, and the spraying temperature is 15°C to 35°C; the drying temperature is 50°C to 80°C, and the drying time is 2h to 12h.

12. Use of the preparation method of the gypsum silica gel composite photocatalytic particles according to any one of claims 1 to 11 in a photocatalytic reaction.

Citation Information

Patent Citations

  • Gypsum fiberboard with adsorption and photocatalytic properties and preparation method and application thereof

    CN110078456A